2023
DOI: 10.1021/acscatal.3c01073
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Mediated Interactions on Alkene Epoxidations in Ti-MFI: Effects of Solvent Identity and Silanol Density

Abstract: Selective alkene oxidation rates within zeolite pores reflect differences in contributions from thermodynamic nonidealities introduced by noncovalent interactions at solid−liquid interfaces and spatial constraints enforced by the zeolite topology. Epoxidation turnover rates for 1-hexene in Ti-MFI zeolite differ by 1000-fold across 10 combinations of solvents, including alcohols and acetonitrile, over Ti-MFI with distinct silanol defect densities. Solvent mediated noncovalent interactions persist across an exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The cleaning procedure was repeated if the H 2 O–H 2 O injection did not give sufficiently low heat rates. Notably, this cleaning procedure is less harsh than treatments using HNO 3 and NaOH ,,,, we reported previously. This method reduces the risk of corrosion and metal dissolution at components of the ITC cell while still leading to measurements with a consistent baseline and high signal-to-noise ratio.…”
Section: Methods and Materialsmentioning
confidence: 86%
See 1 more Smart Citation
“…The cleaning procedure was repeated if the H 2 O–H 2 O injection did not give sufficiently low heat rates. Notably, this cleaning procedure is less harsh than treatments using HNO 3 and NaOH ,,,, we reported previously. This method reduces the risk of corrosion and metal dissolution at components of the ITC cell while still leading to measurements with a consistent baseline and high signal-to-noise ratio.…”
Section: Methods and Materialsmentioning
confidence: 86%
“…Previous studies demonstrate that changing the active metal ,, and intrapore solvent structure ,,,, strongly influence rates and selectivities for alkene epoxidation reactions through changes in the stability of reactive species. Intuitively, changing these variables must also influence the stability of the reactive species for epoxide ring-opening.…”
Section: Resultsmentioning
confidence: 99%
“…Bregante et al reported that the large number of Si-OH groups in Ti-Beta near the Ti active centers disrupted the transition state of epoxidation reaction by hydrogen bonding with H 2 O molecular clusters, generating an entropy increase for the reaction. The highly hydrophilic Ti-Beta gave an epoxidation turnover rate that was 100 times larger than that of hydrophobic Ti-Beta in the 1-hexene epoxidation reaction [22][23][24][25] .…”
Section: Introductionmentioning
confidence: 94%
“…[101] Besides, post-synthetic strategies allow the incorpora-tion of such heteroatoms into zeolite catalysts that cannot be obtained by direct synthesis. [17d,102] In terms of the epoxidation of alkenes and cycloalkenes, titanosilicate zeolites, such as Ti-MWW, [9b,103] Ti-MFI, [104] Ti-Beta, [105] and Ti-MOR, [106] are an excellent class of catalysts. Numerous studies have demonstrated that many factors, including the coordination states and location distributions of Ti active species, hydrophilicity/hydrophobicity of frameworks or active species, micropore sizes of zeolitic channels, etc., influence catalytic activities.…”
Section: Catalytic Applications Of New Materials Derived From Germano...mentioning
confidence: 99%